The prevalence of malocclusion among 11-13 years old children in Foča - Ivanović Tanja; Ivanović Dragan; Nikolić Predrag; Janković Svjetlana; Davidović Bojana; Grujičić Ivana (Serbian Medical Society - Dental Section, Belgrade, 2015)
Introduction Malocclusion is common in children and it has great influence on the quality of life of patients. The aim of this study was to determine the prevalence of malocclusion among 11-13 years old children in the municipality of Foca in Republika Srpska. Material and Methods The study included 81 respondents, 11-13 years old. It was conducted in elementary schools in the municipality of Foča. Respondents underwent clinical examination, alginate impressions of upper and lower jaws were taken and study models analyzed. To determine malocclusion (crowding, spacing, cross bite, deep bite, open bite and occlusion class as per Angle) ICON index (Index of Complexity, Outcome and Need) was used. Results The results showed that 17.3% of respondents had spacing between teeth, 80.2% crowding, 23.4% cross bite, 29.6% deep bite while open bite was present in 2.4% of patients. Occlusion II/1 class by Angle was present in 38.3% of respondents, II/2 class in 12.3% of respondents, Class I occlusion in 40.7% of respondents and III class was found in 2.4% of respondents. Conclusion There was high prevalence of malocclusion in the examined children. It is necessary to implement prevention programs, early treatment of dental caries, prevent premature tooth loss as well as measures of interceptive orthodontics in order to reduce frequency of malocclusion.